Carinata Tolerance to Preemergence and Postemergence Herbicides. (5th October 2017) - Leon, Ramon G.; Ferrell, Jason A.; Mulvaney, Michael J.
Abstract : Carinata is a new biofuel crop that was recently introduced in the southeastern USA as a winter crop. This crop is competitive after canopy closure, but there is a need for weed control options at earlier growth stages. Field experiments were conducted from 2014 to 2016 to determine the safety of several PRE and POST herbicides in carinata. Pendimethalin at 1080 g ai ha −1 applied preplant incorporated (PPI) and PRE caused no carinata injury, or plant density and yield reductions. S -metolachlor was also safe at 694, 1070, 1390, and 2780 g ai ha −1 applied at PRE, 3 d after planting (DAP) and at the 2- to 6-leaf stage. Flumioxazin at 72 g ai ha −1 applied PRE was highly injurious on carinata preventing its establishment. Among the POST herbicides evaluated, clopyralid at 210 g ae ha 1 and clethodim at 136 g ai ha −1 caused minor injury to carinata but did not reduce yield compared to the nontreated control. Acifluorfen at 420 g ai ha −1, bentazon at 840 g ai ha −1, and carfentrazone at 18 g ai ha −1 applied POST to carinata caused 75 to 100% injury. Under stressful conditions (i.e. high summer temperatures) all POST herbicides caused more injury than under more favorable conditions for growth in Florida (i.e. winter). The present study identified pendimethalin, S -metolachlor, clopyralid and clethodim as potential herbicides for weed control in carinata, and flumioxazin, acifluorfen, bentazon, and carfentrazone as herbicides that can be used to control volunteer carinata plants in rotational crops.